Skin diseases are a common problem among young adults (Texas Journal of Medical Science, 2025)
Skin diseases are a major health problem affecting a high proportion of the population in India.[1] Skin diseases can place a heavy emotional and psychological burden on patients that may be far worse than the physical impact.[2] Increased consciousness especially among the youth of their body and beauty further aggravates their anxiety.[3] Many factors determine the pattern and prevalence of cutaneous diseases among the youth such as gender, race, personal hygiene, quality of skin care, environmental milieu and diet.[4] In some instances, patients appear to produce their skin lesions as an outlet for nervous tensions arising from interpersonal conflicts and/or unresolved emotional problems